(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Development of Indian-English literature needs beingdiscussed before the survey of Indian-English novel. Though English is not ourmother tongue, yet our creative writers have got command over English writingand have secured a distinguished position among the renowned writers of Englishliterature. Indian-English literature as critics say, began as an interestingby-product of an eventful encounter in the late eighteenth century between avigorous and enterprising Britain and a stagnant as well as chaotic India.